Disruption of adaptive immunity does not attenuate disease in the Ndufs4(-/-) model of Leigh syndrome. - Allison R Hanaford; Asheema Khanna; Vivian Truong; Katerina James; Ryan Liao; Yihan Chen; Michael Mulholland; Ernst-Bernhard Kayser; Kino Watanabe; Erin Shien Hsieh; Philip G Morgan; Surojit Sarkar; et al. (PLoS ONE)
Leigh syndrome (LS) is the most common pediatric presentation of genetic mitochondrial disease and characterized by neurological and metabolic abnormalities. The hallmark of the disease is the presence of progressive, bilateral, symmetric neurodegenerative lesions in the brainstem and/or basal ganglia. Recent studies in the Ndufs4(-/-) mouse model of LS indicate that disease is causally driven by the immune system. Both microglia and peripherally originating macrophages are enriched in the lesions of Ndufs4(-/-) mice and pharmacologic elimination of these cell types prevents disease indicating a crucial role for innate immune cells. Here, we investigated the role of the adaptive immune system in Ndufs4(-/-) disease pathogenesis. We crossed Ndufs4(-/-) mice with mice expressing a null form of interleukin 2 receptor gamma (Il2rg) and monitored disease onset and progression. Il2rg knockout (KO) mice have dramatically depleted numbers of B-, T-, the adaptive immune system's key cellular actors, and NK-cells. We observed no difference in neurological disease progression or overall survival between Ndufs4(-/-)/Il2rg(WT) and Ndufs4(-/-)/Il2rg(KO) mice, strongly suggesting that T cells, B cells, and NK cells do not play a significant role in CNS disease pathogenesis in Ndufs4(-/-) mice. Combined with previous studies indicating a causal role for macrophages, we conclude that LS CNS pathology is primarily driven by the monocyte/macrophage innate immune system.